Entrepreneurship, personality and sociodemographic variables in Management students of a higher education institute - Kaneko Aguilar, Juan José (2012)
We analyze whether the level of entrepreneurship provides significant differences at the level of personality factors and whether sociodemographic variables to differentiate the level of entrepreneurship. The researchis descriptive comparison, taking a sample of 499 students of International Business Administration. Test was used entrepreneurship ALFA Network. The results show that the level of venture of the total sample is Pc. 57, which places it in the Average range.The area with the highest average Altruism (Pc. 76)and the area with the lowest average Leadership (Pc. 57). We also found that the level of entrepreneurship provides significant differences in level of 13 personality factors (p<0.05). In analyzing whether sociodemographic differenceses tablished enterprise level, it was found that sex, age, employment status of the student and parents’ employment status provides significant differences at the components of entrepreneurship. The residence and socioeconomic variables of the student did not establish significant differences at the level of entrepreneurship and overall factors.